2018
DOI: 10.1073/pnas.1713316115
|View full text |Cite
|
Sign up to set email alerts
|

Integration of speed and time for estimating time to contact

Abstract: SignificanceExisting theories suggest that reacting to dynamic stimuli is made possible by relying on internal estimates of kinematic variables. For example, to catch a bouncing ball the brain relies on the position and speed of the ball. However, when kinematic information is unreliable one may additionally rely on temporal cues. In the bouncing ball example, when visibility is low one may benefit from the temporal information provided by the sound of the bounces. Our work provides evidence that humans rely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 76 publications
(131 reference statements)
7
72
1
Order By: Relevance
“…Consistent with the pattern of results reported in previous studies [18,21,22,25,26], accuracy of the responses decreases with larger TTCs (Figure 4(e)). In other words, increasing the actual TTC results in increasing error in TTC estimation.…”
Section: Ttce (Estimated Ttc) Is the Time Between The Disappearance Osupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the pattern of results reported in previous studies [18,21,22,25,26], accuracy of the responses decreases with larger TTCs (Figure 4(e)). In other words, increasing the actual TTC results in increasing error in TTC estimation.…”
Section: Ttce (Estimated Ttc) Is the Time Between The Disappearance Osupporting
confidence: 91%
“…In future studies, experiments can be designed to study these conditions. Some studies have shown that TTC estimates for each target car speed tends to be biased toward the mean TTC across all target car speeds [24,25,35,36]. We did not observe such pattern in our experiments, maybe because we did not provide participants with feedback on estimation accuracy.…”
Section: Resultscontrasting
confidence: 59%
“…Similarly during pursuit maintenance, it was observed that the ratio 61 between position and velocity error correlates well with the occurrence of saccades and roughly 62 correlates with saccade latency (de Brouwer et al, 2002b). This parameter was originally coined 63 as eye-crossing time, but henceforth referred to as time-to-foveation to parallel the time-to-64 collision parameter in studies of steering control (Regan and Gray, 2000) and the time-to-65 contact parameter in studies of limb control and interception (Chang and Jazayeri, 2018;66 Tresilian, 1995). While time-to-foveation is a useful behavioural correlate, it remains unsuitable 67 as a decision variable due to its instability as velocity errors approach zero (time-to-foveation 68 goes to infinity) and its inability to address how sensory noise is accommodated.…”
Section: Introduction 29mentioning
confidence: 99%
“…The ideal TTCs in our experiment are within that time interval. Our subjects might have been further helped by the fact that the time under occluder was comparable to the visible time before the occlude a factor that is shown to facilitate temporal estimation [7,43]. Some studies have shown that TTC estimates for each condition tends to be biased toward the mean TTC across all conditions [4,6,7,44].…”
Section: Discussionmentioning
confidence: 99%
“…Time to contact (TTC), which is the time it takes for an object to reach an observer or a particular place, is an important factor in a variety of real-world situations, such as catching and hitting balls in games, driving vehicles, or passing through a busy street. The ability to estimate TTC for one object has been assessed in several studies (for example see [1][2][3][4][5][6][7][8][9][10][11][12][13][14]). The accuracy and precision of TTC estimation is related to the time perception ability, which is considered in several studies [6,11,[15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%